Ancient Egyptian Treatise on Power - Vera Vasiljević (University of Belgrade, 2020)
Stefanović, Danijela. 2018. Pouka za Merikarea: staroegipatski traktat o vlasti. Beograd: Evoluta. ISBN 978-86-80912-20-2